Reconstruction of lacerated wound on upper lip in a graded Murrah heifer – A case report - Kamalakar, G.; Mahesh, R.; Prasad, V. Devi (Buffalo Bulletin, 2018)
A 4 year old Graded Murrah Buffalo heifer was presented with extensive lacerated wound on upper lip and nostril on right side that occurred due to an accident. It showed excessive salivation, restlessness, presence of blood clots. The animal was examined thoroughly and prepared for surgery. Reconstructive surgery of upper lip and cheek was carried out under mental nerve block and linear block using Lignocaine hydrochloride. Good surgical technique and effective post operative management made the case successful recovery.